Evolution and Major Criminal Law Amendments Relating to Rape Laws in India: An overview of the evolution and amendments in rape laws in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Rape laws have gone through many changes over the years. This article gives an overview of how rape laws evolved in the world and then how they specifically evolved in India. It also makes recommendations on how to fill in the gaps left by the current legislation, as well as possible fixes. Criminal law in India governs and prohibits the offences or crimes and punishes those who commit crime(s) in accordance with the laws. All the offence or crimes committed in India are all deemed as offences or crimes against the State. In India, generally Criminal law comprises of three major Statutes i.e. Criminal Procedure Code,1973, Indian Evidence Act,1872 and the Indian Penal Code,1860. There are other Criminal laws in India like the Dowry Prevention Act The Narcotic Drugs and Psychopathic Substances Act, etc.